Upaya Meningkatkan Hasil Belajar Siswa Kelas IV pada Pembelajaran Bahasa Indonesia melalui Metode Role Playing di SDN Subahnala - Ahyani, Ahmad (AS-SABIQUN, 2025)
Learning achievements encompassing cognitive, affective, and psychomotor domains remain the primary focus in efforts to improve educational quality. However, at SDN Subahnala, fourth-grade students have yet to fully meet learning targets due to low task completion rates. This study aims to determine the effectiveness of the role-playing approach in enhancing students’ Indonesian language learning outcomes. Employing Classroom Action Research (CAR), the study involved stages of preparation, implementation, observation, and reflection conducted by the teacher to improve student performance. The results demonstrated a significant improvement, with the percentage of students achieving mastery increasing from 60% in the first cycle to 90% in the second. The role-playing approach proved effective not only in meeting Indonesian language learning objectives but also in fostering students’ creativity and motivation. In conclusion, the role-playing method is an effective instructional strategy to enhance learning outcomes and readiness among fourth-grade students at SDN Subahnala.